PROFESSOR STEVE MELLEMA TO SERVE AS FULBRIGHT SCHOLAR IN USM - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, June 2016 – Gustavus Adolphus College, the United States physics professor, Steve Mellema has been selected through the Fulbright Scholar Program to come to Malaysia in 2017 to teach and do research at Universiti Sains Malaysia (USM).